PERBAIKAN SISTEM KERJA UNTUK MENINGKATKAN PRODUKTIVITAS DI IKM TULAKIR FIBERGLASS - Nasution, Amelia Rachmi; purnomo, Hari (Journal Industrial Manufacturing, 2024)
This research was conducted to improve work systems in order to increase productivity by identifying and analyzing the factors that cause worker complaints, as well as minimizing complaints felt by workers using a participatory ergonomics approach in the form of focus group discussions (FGD) so that companies can immediately make improvements to the work system in order to create a work system that is ergonomic, optimal, and according to the needs of workers. Data analysis used statistical tests in the form of a the different tests with the signed rank test to find out differences by comparing pre-test data between initial conditions work system with post test data work system improvement design.Keywords: Worker Complaint; Work System; Ergonomic Participatory; Design